MOLECULAR-PHYSIOLOGICAL MECHANISMS OF THE MAIN FACTORS AND CONDITIONS OF MEMORY DEVELOPMENT, THE IMPORTANCE OF ENVIRONMENTAL FACTORS IN THE FORMATION OF MEMORY (Academicia Globe: Inderscience Research, 2023)
The purpose of the study: by studying the molecular-physiological mechanisms of memory formation, we can find out the capabilities of the human brain. The main thing is that by fully studying the formation of memory, we will know the material foundations of the development of memory, and to consider the importance of memory in the formation of the background, we will consider the role of upbringing and labor to become the owner of a strong memory.